2019
DOI: 10.1111/jfbc.13002
|View full text |Cite
|
Sign up to set email alerts
|

Relative protective activities of quercetin, quercetin‐3‐glucoside, and rutin in alcohol‐induced liver injury

Abstract: Alcoholic liver diseases has been known to be one of the major health risks worldwide. The purpose of this study was aimed to demonstrate the relative protective effect of quercetin, quercetin‐3‐glucoside, and rutin on alcohol‐induced damage in hepatocytes. The hepatotoxicity, antioxidant enzymatic defense mechanisms, and pro‐inflammatory mediators were examined for evaluating the hepatoprotective effects of quercetins in hepG2 cells. The results revealed that quercetin and its glucoside derivatives significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…In addition, chlorogenic acid also attenuated the ethanol-induced oxidative stress by increased anti-oxidant enzymes activities [33]. Rutin exhibited hepatoprotection through elevation of glutathione level, repression of inflammation in HepG2 cells treated with ethanol [34]. In line with these observations, we demonstrated that cotreatment with MLE increased the activities of SOD and GSH-Px of acute alcohol-exposed mice in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, chlorogenic acid also attenuated the ethanol-induced oxidative stress by increased anti-oxidant enzymes activities [33]. Rutin exhibited hepatoprotection through elevation of glutathione level, repression of inflammation in HepG2 cells treated with ethanol [34]. In line with these observations, we demonstrated that cotreatment with MLE increased the activities of SOD and GSH-Px of acute alcohol-exposed mice in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 81%
“…Under physiological conditions, Nrf2 is fixed in the cytoplasm via binding to kelch-like ECH-associated protein 1 (Keap1). Once attacked by ROS, Nrf2 is activated and enters the nucleus, binding to the antioxidant responsive element (ARE) and promoting phase II enzymes (such as HO-1 and SOD) and GSH expression to maintain cellular functions (Lee et al 2019). In the present study, CNE promoted the translocation of Nrf2 into the nucleus, which resulted in an upregulation of GSH, SOD, and HO-1 expression.…”
Section: Discussionmentioning
confidence: 48%
“…In this article, 12 components in CNE were detected by UHPLC-Q-TOF-MS/MS. Among the 12 components, garcinol, pyridoxine, (-)-epicatechin, phloretin, quercetins, rutin, nicotinic acid, taxifolin and rhein showed promising pharmacological activities in the management of inflammation, oxidative stress, and liver disorders (Arauz et al 2015;Behera et al 2016;Ren et al 2016;Bu et al 2018;Roh et al 2018;Huang et al 2019;Lee et al 2019;Sunil and Xu 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Flavoniods including flavonols has been reported to possess multiple health benefits such as protect liver from ALD, NAFLD, intestinal inflammations and others [ 67 , 68 , 69 , 70 ]. Quercetin (3,3′,4′,5,7-pentahydroxyflavone) is one of the most common dietary flavonols present in the apple, onion, black or green tea, herbal medicine, and red wine [ 69 , 70 ]. Many studies have reported that quercetin exerts a beneficial role in non-alcoholic fatty liver disease (NAFLD), ALD, and diabetes mechanically by regulating the expression of lipid-metabolism-related genes and the secretion of inflammatory mediators [ 69 , 70 , 71 , 72 , 73 ].…”
Section: Bioactive Compounds Ameliorate Ald Via Multiple Pathwaysmentioning
confidence: 99%